A remote view of the city: Experiences during the COVID-19 pandemic - Gomes, Ramon Fortunato; Carlucci, Marcelo; Vilela Jr, Adalberto José (Seven Editora, 2023)
The work reports the experience in the teaching of design and representation in architecture and urbanism, from the discipline Perspectivas (cód. 1703.000.295-7), offered in the course of Architecture and Urbanism of the Federal University of Mato Grosso do Sul, campus of Naviraí (MS), during the period of isolation due to the pandemic of COVID-19. Its starting point was the record of urban space through observation. One of the challenges faced was to make the content taught - traditionally associated with workshop practices, on-site visits, and face-to-face orientations - to virtual platforms. It was then decided to conduct the discipline through virtual meetings, using as tools the online meeting platform Google Meet, institutional email, as well as messengers such as WhatsApp (Meta). Thus, after the conclusion of the semester, it was found that the class not only welcomed the adaptation proposal but also engaged in online debates and discussions about the techniques of design and representation in architecture and urbanism. The results were satisfactory and the experience can support new incursions that require the interface of the practice of drawing between screens. DOI:https://doi.org/10.56238/emerrelcovid19-044